"MOSQUITO FAUNA OF IRAN 2- CULEX (DIPTERA: CULICIDAE) " - M. Aaim; A.V. Manouchehri; M.R.Y. Ershadi (Tehran University of Medical Sciences, 1985)
In order to study the mosquito fauna of Iran, and to prepare the temporal as well as the spatial distribution of the Iranian mosquitoes, a comprehensive study has started since 1981. In this program in which more than 60.000 mosquito larvae, from different breeding sites has been studied, 15 species of Culex are reported. These are;Cx. arbieeni, Cx. bitaeniorhynchus, Cx. deserticola, Cx. hortensis, Cx. laticinctus, Cx.mimeticus, Cx. pipiens, Cx. pseudovishnui, Cx.pusillus, Cx. sinaiticus, Cx. sitiens, Cx. territans, Cx. theileri, Cx. tritaeniorhynchus, Cx. univittatus. Culex antennatus Cx. impudicus, Cx. modestus. Cx. torrentium and Cx. vegans which have been reported previously by other workers form Iran have not been found. Since the report on Cx. torrentium and Cx. vegans from Iran has been based solely on larvae, their presence can not be regarded certain due to the great overlap of morphological characters with Cx. pipiens.